A follow-up of gynecological cancer patients: state-of-the-art in Russia - S. N. Puzin; Yu. G. Payanidi; D. S. Ogai; E. V. Korzhevskaya; A. Yu. Kashurnikov; E. V. Vorobyeva (Опухоли женской репродуктивной системы, 2014)
A state-, society-, public health-run follow-up of the population is one of the basic areas of disease prevention. This is particularly important for medicine sections with high morbidity and mortality rates, i. e. for oncology. The paper indicates the basic follow-up principles used in gynecological oncology.